Field screening for drought tolerance in Setaria italica and Panicum miliaceum millet germplasm from Iran - Nejad, Ghasem Mohammadi; Hossein, Vaezi; Eslam, Majidi-Heravan; Babak, Nakhoda; Farokh, Darvish-Kajouri (The Indian Journal of Genetics and Plant Breeding, 2017)
The present study aims at field screening of Proso andFoxtail millet ecotypes for drought tolerance. Accordingly,96 promising millet ecotypes along with four checks wereevaluated under field conditions in Yazd province of Iran.Field experiment was conducted using an incomplete blockdesign (LATTICE) with two replications under droughtstress and control conditions in a period of two years.Multivariate analyses showed variance significant geneticvariation (P < 0.01) among millet ecotypes of Iranian origin.Drought stress tremendously affected grain yield of allgenotypes. The interaction between genotype and droughtwas significant for panicle weight, panicle length and daysto flowering. Based on the results of multivariate analyseswe identified the effective traits which are the foremostfactor responsible for grain yield and dry weight of fodderunder drought stress. Therefore, the selection based onthese traits would be preferable to identify genotypes withhigh yield. Eventually, eight ecotypes with the higher grainyield and 8 with the higher dry weight fodder were foundhighly adoptive under moisture stress conditions. Suchecotypes can be recommended as promising genotypeswhich may eventually be released as new cultivars fordrought-affected areas.